Transformasi Tradisi Mangalehen Tuor dalam Upacara Perkawinan Mandailing Pasca Migrasi ke Kota Medan - Siregar, Pina Hayumi; Fitri, Hadiani; Sumantri, Pulung (Polyscopia, 2024)
This research examines the transformation of the Mangalehen Tuor tradition in Mandailing ethnic wedding ceremonies after migration to Medan City. This tradition has undergone significant adaptation in the context of rapid urbanization and intercultural interactions in urban environments. Changes in the implementation of traditions, such as adjustments to the time and place of implementation, as well as changes in participation and delivery of advice, are the main focus of this research. Factors influencing these changes, such as urbanization, intercultural interactions, the influence of the younger generation, economics, and technology, are analyzed to understand the dynamics of cultural adaptation in a broader context. Despite undergoing transformation, efforts to preserve Mandailing cultural values ??remain a priority, reflected in cultural education efforts, community activities and technology integration. This research provides insight into how ethnic communities manage and maintain their cultural identity amidst the ever-growing challenges of globalization and modernization.